Emodin-induced hepatotoxicity is enhanced by 3-methylcholanthrene through activating aryl hydrocarbon receptor and inducing CYP1A1 in vitro and in vivo. (25th September 2022) - Wang, Meixi; Zhang, Zuqi; Ruan, Panpan; Zhang, Guangchen; Xiao, Chengrong; Wang, Yuguang; Gao, Yue
Abstract: Background & aims: Polygonum multiflorum Thunb. (PMT) is the most common traditional Chinese medicine used to treat multiple diseases, and the hepatotoxicity caused by PMT has made great concern around world. Recent results showed that emodin is the potential toxic components of PMT, but the molecular mechanisms of emodin on liver toxicity remain to be elucidated. Methods: Evaluation of parent- and metabolite-induced cytotoxicity in emodin were compared in L02 cells and mouse model from the perspective of drug metabolizing enzymes. The effect and mechanism of emodin-induced hepatotoxicity were analyzed using electrophoretic mobility shift, promoter reporter, and high content screening. Results: We showed that emodin treatment (360 mg/kg in mice, 50 μM in L02 cells) induced hepatotoxicity and enhanced reactive oxidative stress (ROS) level. Importantly, emodin-induced ROS accumulation and hepatotoxicity were attenuated in the condition of CH223191, a selective inhibitor of aryl hydrocarbon receptor (AhR), and aggravated by 3-methylcholanthrene, a selective activator of AhR. Interestingly, we performed the study on ROS mediated ER stress and mitochondrial dysfunction in emodin-induced hepatotoxicity, the results showed that emodin can decrease MMP and trigger ER stress with Ca 2+ overloading and the expression of ATF4 increasing, further resulted with increased apoptosis in L02 cells and mice mortality rate, while the changes were alleviated by CH223191. Furthermore, the 5-hydroxyemodin, a metabolite by emodin through CYP1A2 enzyme, showed more severe hepatotoxicity compared to emodin. Conclusions: Our results validated that the metabolism of emodin to 5-hydroxyemodin by CYP1A played an important role in the hepatocellular toxicity of emodin and provided evidence that CYP1A1 and AhR could be used to predict and validate patient-specific liver injury of PMT or other herbs containing emodin. Graphical abstract: Image 1 Highlights: 1.CYP1A1 expression was increased in a concentration and time-dependent manner. 2.AhR-CYP1A1 signaling plays an important role in the hepatocellular toxicity of emodin. 3.The emodin promoted hepatotoxicity through inducing ROS/ER stress. 4.5-hydroxyemodin has higher hepatotoxic effects than emodin and other metabolites.